Purification and characterization of two new modification methylases: MClaI from Caryophanon latum L and MTaqI from Thermus aquaticus YTI. - McClelland, M (1981)
A method for detecting Type II modification methylases and determining their methylation site by assaying the ability of methylated DNA to be cleaved by heterologous restriction enzymes is described and applied to the isolation of the restriction modification methylases from Thermus thermophilus HB8, Thermus aquaticus YTI and Caryophanon latum L. M.TaqI is shown to have a methylation specificity identical to M.ThI (TCGmeA). M.ClaI methylates at adenine and protects a subset of TthI sites indicating that it methylates the sequence ATCGmeAT. Methylation by M.ThI also protects against cleavage by SalI, XhoI and at some HindII, AccI and MboI sites.